A Robustness Evaluation Method of Natural Gas Pipeline Network Based on Topological Structure Analysis - Li, Xueyi; Su, Huai; Zhang, Jinjun; Yang, Nan (Frontiers in Energy Research, 2021)
As the total mileage of the pipeline network continues to increase, the topological structure of the natural gas pipeline network will become more and more complex, and then gradually show a trend of system complexity. The complicated topological structure of the pipeline network is likely to cause inherent structural defects in the pipeline network, which has an impact on the safe operation of the pipeline network. At present, research aimed at ensuring the safe and reliable operation of natural gas pipeline networks has become a research hotspot, but very few studies have considered the complexity of natural gas pipeline networks and its possible impacts. In order to understand the complexity of natural gas pipeline network and its behavior when facing structural changes, this paper studies the robustness of natural gas pipeline network based on complex network theory. This paper draws on the methods and experience of complex network robustness research in other research fields, combined with the operation characteristics of natural gas pipeline network, and proposes a robustness evaluation method suitable for natural gas pipeline network. The robustness evaluation method of natural gas pipeline network is helpful to identify the key components of the pipeline network and understand the response of the pipeline network to structural changes, so as to provide a theoretical reference for the safe and stable operation of the natural gas pipeline network. The evaluation results show that the pipeline network can show strong robustness when faced with random attacks represented by pipe accidents or component failures caused by natural disasters, and when faced with targeted attacks represented by terrorist attacks, the robustness of the natural gas pipeline network is very weak. The pipeline network behaves differently in the face of different types of random attacks. The pipeline network is more robust when faced with random attacks represented by component failures than when faced with random attacks represented by pipe accidents caused by natural disasters.